Tanzania in Transition from Nyerere to Mkapa - Havnevik,Kjell (Dar es Salaam Mkuki na Nyota, 2010)
This book is the first comprehensive contribution to understading the character of important societal transition in Tanzania during Benjamin Mkapa's presidency(1995-2005). The analyses of the trajectory of these transitions are conducted against the background of the development model of Tanzania's first president, Julius Nyerere(1961-1985),a model with lasting influence on the country. This approach enables an understanding of continuities and discontinuities in Tanzania over time in areas such as development strategy and ideology, agrarian-land,gender and forestry issues, economic liberalisation, development assistance, corruption and political change.
Keywords: Transition, Agriculture, economic liberilzation, post independence